EFEK FAKTOR DEMOGRAFI DAN KARAKTERISTIK BISNIS ONLINE TERHADAP MINAT PENGAJUAN KREDIT MIKRO - Fermico Karambut; Hartoyo .; Rita Nurmalina; Mukhamad Najib (Universitas Mercu Buana, 2019)
This study aimed to see whether intention of applying for microcredit was influenced by factors of demographic and online business characteristics. The selection of respondents used convenience sampling method by collecting qualitative and descriptive information through online survey to 235 online seller who were members of the Indonesian Online Business Association (APOI). The results of the study using logistic regression analysis proved that only the type of online business that was significantly related to the intention of applying for micro credit. Financial institutions should offer credit products that are suitable for the type of online business to increase intention. Further research based on the type of business and online products will provide better overview of online MSME intnetion models.